2015
DOI: 10.1007/s10597-015-9950-9
|View full text |Cite
|
Sign up to set email alerts
|

Money and Mental Illness: A Study of the Relationship Between Poverty and Serious Psychological Problems

Abstract: a financial contribution per month was granted to 100 individuals with severe mental illnesses for a 9-month period. Assessments of the subjects were made before the start of the intervention and after 7 months' duration. A comparison group including treatment as usual only was followed using the same instruments. Significant improvements were found for depression and anxiety, social networks, and sense of self. No differences in functional level were found. Social initiatives may have treatment and other bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 25 publications
0
39
0
4
Order By: Relevance
“…Examples of community-level interventions include CPIC, which involved 95 organizations in 5 sectors to develop community-wide plans for managing depression, and CTC that supports communities to develop multi-sector coalitions to prevent youth substance use, violence, and delinquency [ 35 •, 103 •]. Other studies acted at the community level by directly providing or influencing resources on a large scale, through cash/food transfers or land revitalization efforts [ 94 , 105 , 106 •, 107 •, 108 , 109 , 110 •].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of community-level interventions include CPIC, which involved 95 organizations in 5 sectors to develop community-wide plans for managing depression, and CTC that supports communities to develop multi-sector coalitions to prevent youth substance use, violence, and delinquency [ 35 •, 103 •]. Other studies acted at the community level by directly providing or influencing resources on a large scale, through cash/food transfers or land revitalization efforts [ 94 , 105 , 106 •, 107 •, 108 , 109 , 110 •].…”
Section: Discussionmentioning
confidence: 99%
“…Social protection studies investigate mental health and other outcomes associated with direct provision of resources in the forms of cash and food transfers [ 105 , 106 •, 107 •, 108 , 109 ]. A neighborhood cluster RCT in Ecuador investigated the effects of such resources on mental well-being and intimate partner violence [ 106 •, 109 ].…”
Section: Mental Health Promotion and Preventionmentioning
confidence: 99%
“…In a study of first-person experiences of hope in relation to dual recovery (Saelør et al, 2015), participants reported that being met with positive expectations from others influenced how they perceived their future. A Swedish study found that persons with mental illness who received a moderate amount of money each month in addition to treatment showed a significant improvement in symptoms, social networks and sense of self, as compared to a "treatment only" control group (Ljungqvist, Topor, Forssell, Svensson, & Davidson, 2015). 'Recovery-nurturing environments' (Glover, 2005) have been suggested as a description of how contextual factors facilitate recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers report links between poverty and depression (Economou et al, 2016;Elliott, 2016;Ljungqvist et al, 2016), and 'problem' debt (Gathergood, 2012). Netuveli et al (2008) consider 3 successive waves of BHPS (for each person), when the person experienced one or more adverse events (illness, becoming single, or poverty) in the second of three years they analysed.…”
Section: Long-term Depression Caused By Financial Stressmentioning
confidence: 99%